2014
DOI: 10.1016/j.bbamem.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the interaction of CHAPS and Triton X-100 with the erythrocyte membrane

Abstract: The zwitterionic detergent CHAPS, a derivative of the bile salts, is widely used in membrane protein solubilization. It is a "facial" detergent, having a hydrophilic side and a hydrophobic back. The objective of this work is to characterize the interaction of CHAPS with a cell membrane. To this aim, erythrocytes were incubated with a wide range of detergent concentrations in order to determine CHAPS partition behavior, and its effects on membrane lipid order, hemolytic effects, and the solubilization of membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 31 publications
1
40
0
2
Order By: Relevance
“…have also reported that hemoglobin release and solubilization of phospholipids/cholesterol evoked by TX-100 were processes not directly correlated, once hemoglobin release preceded solubilization. They confirmed our hypothesis that hemoglobin is released from erythrocytes through holes created by the partition and fast segregation of TX-100 to cholesterol poor (liquid disordered, Ld) regions of the membrane, while most of the lipids remained insoluble (Rodi et al 2014). Those authors have found different results with the zwitterionic and weak solubilizer CHAPS, to which hemoglobin release and lipid solubilization occurred at the same detergent concentration range.…”
Section: Measuring the Bilayer/micelle Transition During Detergent-insupporting
confidence: 73%
See 3 more Smart Citations
“…have also reported that hemoglobin release and solubilization of phospholipids/cholesterol evoked by TX-100 were processes not directly correlated, once hemoglobin release preceded solubilization. They confirmed our hypothesis that hemoglobin is released from erythrocytes through holes created by the partition and fast segregation of TX-100 to cholesterol poor (liquid disordered, Ld) regions of the membrane, while most of the lipids remained insoluble (Rodi et al 2014). Those authors have found different results with the zwitterionic and weak solubilizer CHAPS, to which hemoglobin release and lipid solubilization occurred at the same detergent concentration range.…”
Section: Measuring the Bilayer/micelle Transition During Detergent-insupporting
confidence: 73%
“…TX-100 is known to preferentially solubilize phospholipids from the inner leaflet of the cell membrane (Ingelmo-Torres et al 2009;Koumanov et al 2005;Lichtenberg et al 2005) while Brij detergents are not as selective as TX-100 (Schuck et al 2003). Rodi et al (2014) have also demonstrated that TX-100 incorporates and solubilize lipid components from the erythrocyte membranes in a different way compared with CHAPS (a zwitterionic detergent). Those results also indicate that TX-100 is able to flip to the inner leaflet and incorporate in poor cholesterol regions of the membrane, while CHAPS probably due to its charges is prevented from flip-flop and thus acts on the surface of the erythrocyte membrane (Rodi et al 2014).…”
Section: Drms-associated Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…The damage of plasma membrane following a TX-100 exposure was further evaluated using the hemolysis and solubilized phospholipids (PLs) assay as standard techniques. [31] Trends were similar between the hemolytic activity and the amount of solubilized PLs on challenge by TX-100 (Figure 5(C) and 5(D)). The concentration dependence of these values was fitted by the logistic function.…”
Section: Resultsmentioning
confidence: 60%